A cone-beam computed tomography study of deformational plagiocephaly and its influence on condylar position and menton deviation in subjects with Class I skeletal pattern - Kang, He-Kyong; Cheema, Jasmine; Kaczynski, Richard; Pangrazio-Kulbersh, Valmy (American journal of orthodontics and dentofacial orthopedics, 2025)
This study aimed to explore the distribution of deformational plagiocephaly in subjects with Class I skeletal pattern and the relationships of cranial vault asymmetry with menton deviation, condylar anteroposterior (AP) position and condylar angulation using cone-beam computed tomography images. Approximately 135 pretreatment records of patients with skeletal Class I growth patterns from the University of Detroit Mercy were examined using Anatomage Invivo6 software. The midsagittal plane constructed by nasion, incisive foramen, and basion was used to evaluate the asymmetry of the cranium vault, condyles, and menton deviation. For each patient, the radiographic cranial vault asymmetry (RCVA) was calculated and compared against condylar and chin measurements: the horizontal condylar angle, AP positions of the condyles, and menton deviation. The Pearson correlation showed no direct correlation between RCVA and the mandibular variables (menton deviation and condylar measurements). The only mandibular variable that showed interaction with RCVA was the AP position discrepancy between the right and left condyles. The severity of cranial vault asymmetry did not correlate to the asymmetry of the horizontal condylar angle, AP condylar position, and chin deviation. A tendency toward a relation between cranial asymmetry and AP positions of right and left condyles was observed. •Cone-beam computed tomography images of 135 subjects with Class I growth patterns were studied.•RCVA was not correlated with menton deviation and condylar angulation.•A tendency toward a relation between RCVA and condylar anteroposterior position was observed.